Bevacizumab may improve quality of life, but not overall survival in glioblastoma: an epidemiological study. (30th March 2018) - Gramatzki, D; Roth, P; Rushing, E J; Weller, J; Andratschke, N; Hofer, S; Korol, D; Regli, L; Pangalu, A; Pless, M; Oberle, J; Bernays, R; et al.
Abstract: Background: The vascular endothelial growth factor antibody bevacizumab (Avastin ® ), received approval for the treatment of recurrent glioblastoma in many countries including the USA and Switzerland, but not the European Union, in 2009. Here, we explored the hypothesis that the approval of bevacizumab improved outcome with glioblastoma on a population level. Patients and methods: The prognostic significance of epidemiological, molecular genetic, and clinical data including treatment for glioblastoma patients diagnosed from 2010 to 2014 in the Canton of Zurich, Switzerland, was retrospectively analyzed using log-rank test and Cox proportional hazards models. Data were compared with data for the years 2005–2009. Results: In total, 310 glioblastoma patients were identified in the years 2010–2014. Median overall survival was 13.5 months for patients with known isocitrate dehydrogenase ( IDH ) wild-type (wt) (IDH1 R132H -non-mutant) tumors ( N = 248), compared with 11.3 months for IDH wt patients ( P = 0.761) before (2005-2009). In the IDH wt cohort, bevacizumab use at any time increased from 19% in 2005–2009 to 49% in 2010–2014. Multivariate analysis did not identify bevacizumab exposure at any time to be associated with survival. Yet, upon the second-line treatment, baseline doses of corticosteroids were reduced by more than half in 83% of patients on bevacizumab compared with 48% of the patients treated with bevacizumab-free regimens ( P = 0.007). Conclusion: This epidemiological study of a small, but clinically well-annotated patient cohort fails to support the assumption that the strong increase of bevacizumab use since 2010 improved survival in glioblastoma although clinical benefit associated with decreased steroid use may have been achieved.